IMPLIKASI RELASI EKSPLORATIF (ALAQAH AL-TASKHIR) DALAM PENDIDIKAN ISLAM: TELAAH FILOSOFIS ATAS PEMIKIRAN MAJID IRSAN AL-KILANI - Rahendra Maya (Edukasi Islami: Jurnal Pendidikan Islam, 2018)
AbstractThis article examines Makhjid 'Irsân Al-Kîlânî perspective on explorative relationships between human beings as servants of Allah S.W.T. with the universe or the universe that surrounds and is around them ('alâqah al-taskhîr,' alâqah baina al-insân wa al-kaun); in a frame of worship to Him ('alâqah al-'ibâdah,' alâqah baina al-insân wa Al-Khâliq). The original and pithy thought of Al-Kîlânî is primarily derived from his work entitled Al-Tarbiyah Al-Islâmiyyah Philosophy: Dirâsah Muqâranah baina Falsafah Al-Tarbiyah Al-Islâmiyyah wa Al-Falsafât Al-Tarbawiyyah Al-Mu'âshirah and Ahdâf Al-Tarbiyah Al-Islâmiyyah fî Tarbiyah Al-Fard wa Ikhrâj Al-Ummah wa Tanmiyah Al-Ukhuwwah Al-Insâniyyah supported by several other educational works. The explorative relation ('alâqah al-taskhîr) described by Al-Kîlânî is, among other things, related to the nature of al-taskhîr, the essential objective of al-taskhîr, al-taskhîr objectivity, and the implications of al-taskhîr relations.Keyword: al-taskhîr, 'alâqah al-taskhîr, philosophical, Islamic education.   AbstraksiArtikel ini mengkaji perspektif Mâjid ’Irsân Al-Kîlânî tentang relasi eksploratif antara manusia sebagai hamba Allah S.W.T. dengan alam semesta atau jagat raya yang melingkupi dan ada di sekitar mereka (’alâqah al-taskhîr, ’alâqah baina al-insân wa al-kaun); dalam bingkai peribadatan kepada-Nya (’alâqah al-’ibâdah, ’alâqah baina al-insân wa Al-Khâliq). Pemikiran orisinil dan bernas dari Al-Kîlânî tersebut utamanya berasal dari karyanya yang berjudul Falsafah Al-Tarbiyah Al-Islâmiyyah: Dirâsah Muqâranah baina Falsafah Al-Tarbiyah Al-Islâmiyyah wa Al-Falsafât Al-Tarbawiyyah Al-Mu’âshirah dan Ahdâf Al-Tarbiyah Al-Islâmiyyah fî Tarbiyah Al-Fard wa Ikhrâj Al-Ummah wa Tanmiyah Al-Ukhuwwah Al-Insâniyyah dengan didukung beberapa karya edukatifnya yang lain. Relasi eksploratif (’alâqah al-taskhîr) yang dideskripsikan Al-Kîlânî antara lain berkaitan dengan hakikat al-taskhîr, tujuan esensial al-taskhîr, objektifitas al-taskhîr, dan implikasi relasi al-taskhîr.Keyword: al-taskhîr, ’alâqah al-taskhîr, filosofis, pendidikan Islam.